Оцінювання управлінського персоналу як основного джерела забезпечення кадрової безпеки підприємства - Карковська, В. Я. (Видавництво Львівської політехніки, 2015)
В умовах забезпечення економічної безпеки підприємства вагоме місце відведено кадровій безпеці. Основним джерелам забезпечення ефективності кадрової безпеки підприємства є комплексне оцінювання управлінського персоналу. В статті проілюстровано процес оцінювання управлінського персоналу як основного джерела забезпечення кадрової безпеки підприємства з розмежуванням його на певні етапи. In terms of ensuring the enterprise economic security the personnel safety plays an important role. The main source of providing the enterprise personnel safety efficiency is a comprehensive evaluation of the enterprise managerial personnel. The article illustrates the process of managerial personnel evaluation as the main source of providing the enterprise security, with this process being divided into certain stages. The main purpose of evaluating managerial staff as a source of the enterprise personnel security is providing the most effective ways to implement the enterprise security strategy. In the process of achieving this goal the following tasks should be performed: ensuring the rapid economic development of the enterprise due to effectiveness of managerial personnel; ensuring the revenue maximization due to effective implementation of management decisions; managing personnel risks; ensuring enterprise financial stability and solvency due to managerial personnel effectiveness; searching for the ways to accelerate the enterprise personnel security programmes implementation. The management effectiveness of the personnel component is the initial condition for realizing economic security and its strategy, as it supports this realization with the relevant material and labor resources. This trend of the enterprise activities aims to accomplish the following tasks: to quickly and accurately adapt the activities of the enterprise to changing market conditions, to the markets of appropriate material resources and means of production; to make appropriate adjustments to the strategic and operational plans of the enterprise; to minimize costs of the necessity to change plans; to plan requirements in specialists; to professionally develop specialists; to develop methods of assessing personnel performance and to implement conclusions made from this assessment. The development strategy of any enterprise since its formation assumes steady economic growth through effective management activities. The effectively built management process is a major factor and a prerequisite to ensure both enterprise successful operation and maintenance of a high level of competitive advantages of the enterprise. There is a direct connection between the efficiency of administrative activities at the enterprise and its economic development. This especially applies to enterprises whose position in the market economy is changed fundamentally, the process being accompanied by the need to introduce new directions of management improvement. The main purpose of evaluating managerial personnel is to identify problems in the management personnel activities to ensure the appropriate level of personnel security of the enterprise and the ways to overcome them. The process of evaluating the managerial personnel should be purposeful, i.e. it should be aimed at achieving the set goal; it should also be active, dynamic and flexible. The system of goals should be ordered according to the terms and mechanisms of continuous reproduction, i.e it should be realistic, clear, measurable, and urgent. The process of evaluating managerial personnel as the main source of ensuring the enterprise personnel security allows to form its optimal structure, to include the most necessary components, and to depict it schematically. On this basis it is possible to ensure evaluation of the effectiveness of managerial personnel and functioning of personnel security, without material and financial costs. The presented managerial personnel evaluation stages will be used in further studies on finding effective ways to ensure the necessary level of the enterprise personnel security.
Management personnel evaluation as the main source of ensuring enterprise personnel security
Keywords: оцінювання управлінського персоналу; кадрова безпека; принципи; методи; суб’єкти та об’єкти оцінювання; assessment management; personnel security; principles; methods; subjects and objects of evaluation